SPORTS CLUSTERS AS A TOOL FOR THE STRATEGIC DEVELOPMENT OF MASS SPORTS IN THE REGIONS OF THE RUSSIAN FEDERATION - Gureeva E.A.; Petrenko E.S.; Goncharova N.Yu.; Alatyreva Ya.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the strategic features of the development of mass sports in the regions of the Russian Federation based on the use of a cluster model. Methods and structure of the study. The scientific work is based on the application of the region positioning model depending on the degree of development of mass sports, which uses the indicator "the share of the population of the region systematically involved in physical culture and sports in the total population of the region" (hereinafter referred to as the share of the population systematically involved in sports) and the growth rate this figure for five years. Verification of the model was carried out on the positioning of 12 regions of the Russian Federation. Results and conclusions. Four groups of regions have been identified depending on the degree of development of mass sports, two groups of which reflect the favorable situation in the development of mass sports in the region. Thus, a favorable situation with the development of mass sports is noted in the Belgorod region, the Krasnodar region and the Republic of Dagestan. High growth rates are observed in the Primorsky and Stavropol Territories, the Republic of Bashkortostan and the Kaluga Region. The boundary value was revealed in the Khanty-Mansiysk Autonomous Okrug - Yugra. The conclusions of this study make it possible to substantiate the need for the use of specific tools for the development of mass sports for each group of regions. Sports clusters of various structures, taking into account the socio-economic, ethnic, socio-cultural and natural-climatic features of the region, can serve as an instrument for the development strategy of mass sports.